Developing Islamic Value-Based Arabic Speaking Materials Using Flashcards: تطوير مواد تعليمية لمهارة الكلام مستندة إلى القيم الإسلامية باستخدام البطاقات - Wijaya, Mualim; Ulfah, Yeniati (Institut Agama Islam Negeri Palangka Raya, 2025)
Speaking skills are a critical component in learning Arabic as a foreign language, yet they are often neglected in curricula and teaching materials that tend to be text-dominant and lacking in Islamic religious context. This gap causes difficulties for students in achieving oral proficiency that aligns with their academic and spiritual needs. This development research aims to create a speaking skills textbook that integrates Islamic values and utilizes picture cards as an interactive medium for foreign learners in the Arabic Language Education Study Program at Universitas Islam Nurul Jadid. Adapting the Borg & Gall model, the research involved needs analysis, design, expert validation, and limited trials. The needs analysis confirmed the inadequate attention given to speaking skills and a strong desire for religiously nuanced teaching materials. A trial with 17 students showed a statistically significant improvement, indicating the product's effectiveness. The study concludes that integrating cultural values with a visual-interactive pedagogical approach can enhance oral skills learning. It is hoped this product can be adapted more broadly and combined with digital media.